2009
DOI: 10.1152/jn.91196.2008
|View full text |Cite
|
Sign up to set email alerts
|

Tuning to Interaural Time Difference and Frequency Differs Between the Auditory Arcopallium and the External Nucleus of the Inferior Colliculus

Abstract: Vonderschen K, Wagner H. Tuning to interaural time difference and frequency differs between the auditory arcopallium and the external nucleus of the inferior colliculus. J Neurophysiol 101: 2348 -2361, 2009. First published March 4, 2009 doi:10.1152/jn.91196.2008. Barn owls process sound-localization information in two parallel pathways, the midbrain and the forebrain pathway. Exctracellular recordings of neural responses to auditory stimuli from far advanced stations of these pathways, the auditory arcopalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 62 publications
(84 reference statements)
3
36
0
Order By: Relevance
“…Because midbrain space-specific neurons have only been reported in ICx, the spatial tuning in the thalamus is likely computed within the thalamus itself. In addition, ICx neurons do not respond to frequencies as low and as high as those found in Ov and the forebrain (Pérez and Peña 2006;Vonderschen and Wagner 2009). This indicates that frequency convergence already differs from the midbrain at the entryway to the forebrain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because midbrain space-specific neurons have only been reported in ICx, the spatial tuning in the thalamus is likely computed within the thalamus itself. In addition, ICx neurons do not respond to frequencies as low and as high as those found in Ov and the forebrain (Pérez and Peña 2006;Vonderschen and Wagner 2009). This indicates that frequency convergence already differs from the midbrain at the entryway to the forebrain.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory spatial tuning at the crossroads of the midbrain and forebrain. J Neurophysiol 102: 1472-1482, 2009. First published July 1, 2009 doi:10.1152/jn.00400.2009.…”
mentioning
confidence: 99%
“…Fig. 2, also Pérez et al, 2009;Vonderschen and Wagner, 2009). ICX neurons typically respond to frequencies Ͼ3 kHz.…”
Section: Contributions Of Low-frequency and High-frequency Ranges To mentioning
confidence: 94%
“…Recent findings indicated that low-frequency information substantially impacts ITD processing in the forebrain (Pérez and Peña, 2006;Vonderschen and Wagner, 2009). Thus, a parsimonious explanation for the emergence of nonzero CPs at the endpoint of the forebrain pathway lies in the remodeling of information through convergence of inputs from a broad frequency range (Fig.…”
Section: Frequency-dependent Delays In Single Neuronsmentioning
confidence: 99%
See 1 more Smart Citation